Analisis Pemberian Air Irigasi pada Daerah Layanan Petak Tersier dengan Luas Maksimal 50 Ha - Yanto, Fery; Ridwan, Ridwan; Rosadi, R.A. Bustomi; Amin, M. (abe.fp.unila.ac.id, 2024)
Irrigation network is one of the determining factors that are important in regulating the supply of water to agricultural land. If the network cannot meet the needs of irrigation water on agricultural lands, will cause a decrease in problem pruductifity on agricultural land. The purpose of this research is to know the water discharge and assess the effectiveness of the grant of the irrigation water tertiary swath size of maximum 50 ha on rice plant growth phase. The irrigation network that can not meet the needs of irrigation area water means the granting of water in irrigation service areas is not appropriate. The methods used in this research is a survey method. discharge measurement carried out at specified tertiary irrigation channels at random in the field. Results of the study showed measurable discharge on tertiary buildings by using door type Crump of de Gruyter is larger than the discharge should be available, the effectiveness of the grant of the irrigation water which is pretty good going on in the area with extensive irrigation services 30 – 40 ha, with a value of efficiency reached 68%. Keywords: Irrigation network, Kota Gajah, Performance of irrigation, Tertiary level irrigation